A combined experimental and theoretical study on a single, unsupported oxo-bridged Mn(iii, iii) dimer coordinated to two iminobenzosemiquinone π-radical anions. Issue 25 (4th June 2021) - Paul, Ganesh Chandra; Sarkar, Prasenjit; Sarmah, Amrit; Shaw, Prantick; Maity, Suvendu; Mukherjee, Chandan
Abstract : An unprecedented two iminosemiquionone radical-coordinated (μ-oxo)-bridged dinuclear, high-spin Mn(iii, iii ) complex (1 ) was reported. Metal-centric oxidations and ligand-based reductions are confirmed by spectroscopic and DFT-based calculations. Abstract : Ligand H2 L AP comprises a non-innocent 2-aminophenol unit and an innocent bis(pyridin-2-ylmethyl)amine unit. The ligand, upon reaction with an equivalent amount of Mn(ClO4 )2 ·6H2 O in the presence of Et3 N under air in MeOH, provided a mono(oxo)-bridged dinuclear Mn2 complex ({[(L ISQ )Mn III –O–Mn III (L ISQ )][(ClO4 )]2 }; 1 ). X-ray crystal structure analysis of complex 1 revealed that in the dicationic unit, the physical oxidation state of each Mn ion was +III and the 2-aminophenol unit of ligand H2 L AP was in its one-electron oxidized iminobenzosemiquinone form. 1 H-NMR measurement of complex 1 confirmed that the complex acquired a diamagnetic ground state ( S t = 0). Thus, antiferromagnetic couplings among the paramagnetic centers were realized. The UV-Vis-NIR spectrum of complex 1 was consisted of ligand-to-metal charge-transfer transitions in the visible region, while ligand-to-metal and metal-to-ligand charge-transfer transitions were noticed in the near-infrared region due to the presence of iminobenzosemiquinone radical units. The cyclic voltammogram of the complex showed three one-electron oxidation waves and two one-electron reduction waves. While the first two oxidation processes were metal-based, the two successive reductions were ligand-centered. DFT-based theoretical studies confirmed the assignment.